Pengaruh Fasilitas Kerja Dan Kerjasama Tim Terhadap Kinerja Aparatur Desa di Kecamatan Nita Kabupaten Sikka (Studi Kasus Pada Desa Nita, Desa Nitakloang, Desa Tebuk dan Desa Lusitada) - Mariani Aurelia Dua Kedong; Walter Obon; Vinsensius Ama Muda (Lembaga Pengembangan Kinerja Dosen, 2023)
The background of this research was the village administration performance in Nita Sub-district had not been maximized. This research aimed to (1) determine the description of village administration performance, work facilities, and teamwork of the villages in Nita Sub-district, Sikka Regency; and (2) analyze the influence of work facilities and teamwork on the village administration performance in Nita Sub-district, Sikka Regency both partially and simultaneously. The population in this research was village apparatus in Nita Sub-district as many as 36 people. This research was conducted by census or saturated due to limited population. Data were collected through questionnaires and analyzed through descriptive and inferential statistical methods, namely multiple linear regression. The hypothesis testing was done through the t-test and F-test. The results of descriptive analysis showed that the variables of employee performance, work facilities, and teamwork were categorized as good. The statistical results of the t-test showed that partially the work facility and teamwork variables had a significant effect on employee performace. The results of the F-test statistic showed that simultaneously the work facility and teamwork variables had a significant effect on the employees’ performance. The results of the determination analysis indicated that the two independent variables in this research could explain the fluctuation of village administration performance in Nita Sub-district by 56,3%.